The Banking Commission as a Legal Mechanism to Regulate the Banking Sector - A Comparative Study- - Chemachema, Hadjer (Journal of Human Sciences, 2021)
Reforming the Algerian banking system is one of the most important issues raised in a world characterized by financial market liberalization, technological development, and the globalization of the economy. This idea of control came to address the shortcomings of traditional mechanisms in governance, which made it necessary for the Algerian legislature to keep up with this development by creating regulatory bodies for banking activity, among them the Banking Commission. The latter is inspired by French legislation, which plays a monitoring and preventive role in the extent to which banks and financial institutions respect the legislative and regulatory provisions of the good conduct of the profession, and another disciplinary role that deters anyone who violates those provisions. This study therefore aims to highlight the legal system of the Banking Commission by addressing its composition, nature, and the role entrusted to it comparing it to french legislation.